Physics matters - "England, Nick" (Hodder And Stoughton London, 2000)
This text has been updated to meet the demands of the new syllabuses for GCSE Physics introduced after the implementation of the National Curriculum. Two new sections on Earth and space and Earth and atmosphere have been added. It is updated to account for changes in the technological world.